Examining youth participation in the electoral process of Zimbabwe from the period 2000 - 2013: case study of Kuwadzana - Chigwenjere, Lisben Tawanda (Midlands State University, 2017)
Youths in Zimbabwe constitute the majority of the population but are either sidelined or alienated from electoral processes, weakening the very ground-works of citizenship and democracy. Young people in Zimbabwe are facing different challenges ranging from unemployment, poverty, drug abuse, crime, prostitution, lack of funding for tertiary education, and HIV/AIDS. These problems have been exacerbated by an undemocratic and unyielding ZANU PF government which has been in power since 1980. Young people in Zimbabwe have been exploited by the ZANU PF party and made into ruffians responsible for attacking and hurting members and supporters of the opposition party, the Movement for Democratic Change (MDC). Factors such as political violence have contributed to the fear of politics among the youth in Zimbabwe, scaring them away from the electoral process. This has created a “participatory crisis” in Zimbabwe which is weakening the very groundworks of citizenship and democracy.